Integrative approach and education in the process interdisciplinary dependence of application pedagogical basics (Eurasian Journal of Learning and Academic Teaching, 2023)
This is it in the article integrative approach and education in the process interdisciplinary dependence of application pedagogical basics about feedback stated .